2022
DOI: 10.1103/physrevb.105.064512
|View full text |Cite
|
Sign up to set email alerts
|

Two-gap s± -wave superconductivity at an oxide interface

Abstract: After half a century of debate, superconductivity in doped SrTiO 3 has come to the fore again with the discovery of interfacial superconductivity in the LaAlO 3 /SrTiO 3 heterostructures. While these interfaces share the interesting properties of bulk SrTiO 3 , quantum confinement generates a complex band structure involving bands with different orbital symmetries whose occupancy is tunable by electrostating doping. Multigap superconductivity has been predicted to emerge in LaAlO 3 /SrTiO 3 at large doping, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 65 publications
(91 reference statements)
1
5
0
Order By: Relevance
“…[37] Trevisan et al suggested that such mechanism could be responsible for the reduction of T c in the overdoped regime of (001)-oriented LaAlO 3 /SrTiO 3 interfaces. [13] The recent observation of single-gap to two-gap superconductivity transition associated to a decrease in T c in a (110)-oriented LaAlO 3 /SrTiO 3 interface, consistent with s ± -wave superconductivity, supports this proposal, [16,17] although this system has some significant differences in the band structure with respect to the conventional (001)-orientation discussed here. Following this approach, we interpret the optimal doping point c max T in LaAlO 3 /SrTiO 3 as the filling threshold of a new band, which accommodates a second superconducting gap repulsively coupled to the first one.…”
Section: Schrödinger-poisson Numerical Simulationssupporting
confidence: 75%
See 3 more Smart Citations
“…[37] Trevisan et al suggested that such mechanism could be responsible for the reduction of T c in the overdoped regime of (001)-oriented LaAlO 3 /SrTiO 3 interfaces. [13] The recent observation of single-gap to two-gap superconductivity transition associated to a decrease in T c in a (110)-oriented LaAlO 3 /SrTiO 3 interface, consistent with s ± -wave superconductivity, supports this proposal, [16,17] although this system has some significant differences in the band structure with respect to the conventional (001)-orientation discussed here. Following this approach, we interpret the optimal doping point c max T in LaAlO 3 /SrTiO 3 as the filling threshold of a new band, which accommodates a second superconducting gap repulsively coupled to the first one.…”
Section: Schrödinger-poisson Numerical Simulationssupporting
confidence: 75%
“…[ 13 ] and observed in (110)‐oriented interfaces. [ 16,17 ] We therefore expect T c to decrease in the overdoped region because of interband scattering (point C). In contrast, for Δ V TG > 0, the confining potential well becomes sharper as suggested in Figure 2a, and the dxy${d_{{\rm{xy}}}}$ subband is repelled to higher energy (panel 5d).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth to try the effect of non-magnetic impurity on the superconducting transition temperature. It has been shown in [65][66][67] that T c suppresses drastically for s +− gap symmetry due to promoted pair breaking because of interband impurity scattering, whereas T c changes only slightly in case of s ++ symmetry.…”
Section: Soft Pcs Measurementsmentioning
confidence: 99%